A psychometric investigation of the personality traits of a group of migraine sufferers - Meyer, Else Carol (Department of Psychology, 2023)
The aim of this study is to investigate the personality traits of a group of migraine sufferers using the psychometric method. The migraine, normal and psychosomatic control groups were tested on the Hysteroid-Obsessoid Questionnaire, the California Psychological Inventory and the Sixteen Personality Factor Test. The results indicate that the three groups do not differ significantly in terms of scores obtained on any of the three tests. The results are interpreted in terms of previous studies. In certain instances, they are similar to those obtained in other studies. Where the results of this study differ from those of previous studies, these differences are interpreted in terms of sample differences and differences in the nature of the measuring instruments. The results are also interpreted in terms of recent re-evaluations of concepts in psychosomatic medicine and migraine research. Two alternative approaches are suggested for future research. It is suggested that researchers attempt to identify whether meaningful differentiations exist within the migraine population. It is also suggested that researchers adopt a situationally based approach to the understanding of the personality of migraine sufferers.